1986
DOI: 10.1128/jvi.57.1.71-80.1986
|View full text |Cite
|
Sign up to set email alerts
|

Rapid emergence of novel antigenic and genetic variants of equine infectious anemia virus during persistent infection

Abstract: Previous results from our laboratory have demonstrated that equine infectious anemia virus displays structural variations in its surface glycoproteins and RNA genome during passage and chronic infections in experimentally infected Shetland ponies (Montelaro et al., J. Biol. Chem. 259:10539-10544, 1984; Payne et al., J. Gen. Virol. 65:1395-1399, 1984). The present study was undertaken to obtain an antigenic and biochemical characterization of equine infectious anemia virus isolates recovered from an experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(78 citation statements)
references
References 53 publications
4
73
1
Order By: Relevance
“…Quarantine rules were based on epidemiologic and entomologic evidence of mechanical transmission of EIAV by hematophagous insects (Hawkins et al, 1973;Hawkins et al, 1976;Issel et al, 1984;Stein et al, 1942). In the 1970s researchers provided the initial evidence that sequential febrile episodes were associated with the emergence of novel antigenic strains of the virus (McGuire et al, 1987;Payne et al, 1984;Salinovich et al, 1986;Kono et al, 1973). Subsequently EIAV was the first lentivirus in which antigenic variation of neutralization-sensitive epitopes was documented (McGuire et al, 1987;Salinovich et al, 1986;Kono et al, 1973).…”
Section: Historical Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Quarantine rules were based on epidemiologic and entomologic evidence of mechanical transmission of EIAV by hematophagous insects (Hawkins et al, 1973;Hawkins et al, 1976;Issel et al, 1984;Stein et al, 1942). In the 1970s researchers provided the initial evidence that sequential febrile episodes were associated with the emergence of novel antigenic strains of the virus (McGuire et al, 1987;Payne et al, 1984;Salinovich et al, 1986;Kono et al, 1973). Subsequently EIAV was the first lentivirus in which antigenic variation of neutralization-sensitive epitopes was documented (McGuire et al, 1987;Salinovich et al, 1986;Kono et al, 1973).…”
Section: Historical Overviewmentioning
confidence: 99%
“…In the 1970s researchers provided the initial evidence that sequential febrile episodes were associated with the emergence of novel antigenic strains of the virus (McGuire et al, 1987;Payne et al, 1984;Salinovich et al, 1986;Kono et al, 1973). Subsequently EIAV was the first lentivirus in which antigenic variation of neutralization-sensitive epitopes was documented (McGuire et al, 1987;Salinovich et al, 1986;Kono et al, 1973). Pathogenesis research revealed that many of the clinical signs of disease were a result of widespread activation of the immune system McGuire et al, 1972).…”
Section: Historical Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Variants of hepatitis A virus isolated from persistently-infected monkey cells were cytophatic (Lemon et al, 1991). The appearance of variants which evade immune surveillance has been reported for visna view of sheep (Stanley et al, 1988) and for equine infectious anaemia virus (Salinovich et al, 1986).…”
Section: Viral Genomes Of Persistent Infections Vary In Theirmentioning
confidence: 87%
“…Virus populations of persistent infections are genetically variable. This has been repeatedly observed since the development of techniques for sequencing nucleic acids; recent examples include parainfluenza virus 3 (Murphy, Dimock & Kang, 1991), hepatitis B virus (Groetzinger & Will, 1992), equine infectious anaemia virus (Salinovich et al, 1986;Alexandersen & Carpenter, 1991), visna virus of sheep (Clements et aL, 1980) and caprine arthritis encephalitis virus (Ellis et aL, 1987). RNA viruses as a whole are so variable, in large part because the infidelity of RNA polymerases yields a high mutation rate, that their populations should not be thought of as comprising a basic type around which some variation occurs, but rather as a mixture of indefinite and constantly changing composition (Domingo et al, 1985).…”
Section: The Evolution Of Viruses Within Hostsmentioning
confidence: 89%